A Study of Professional Development and In-Service Teacher Training Programs at School Level in the Punjab - Qaisra, Rani; Haider, Syed Zubair (Pakistan Journal of Humanities and Social Sciences, 2024)
The main objective of this study is to investigate the importance, impacts, and challenges faced by teachers when carrying out in-service training programs. Using a descriptive research methodology, data was collected from 291 head teachers who were randomly selected through a questionnaire that was prepared specifically for this study. The key findings suggest that the gender and location of head teachers had no impact on their perspectives regarding the significance of in-service training for professional growth. Nevertheless, the way in which in-service training affects the professional growth of teachers differs greatly among districts. The study suggests that we should view professional development as a continuous process, where educational departments provide numerous opportunities for skill enhancement. Teachers are strongly urged to prioritize training programs and actively engage in all accessible opportunities, even if they require personal financial investment. In addition, it is essential for head teachers to frequently provide training programs that specifically target the competencies needed by their teachers.